PENGARUH KOMPETENSI PERSONAL DAN MANAJEMEN PEMBELAJARAN TERHADAP KEPUASAN KERJA GURU SMP DI KECAMATAN BANDAR SRIBHAWONO LAMPUNG TIMUR - Marliah, Siti (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2018)
This research aims to analyze: 1) The influence of personal competence on teacher work satisfaction, 2) The influence of learning management on teacher work satisfaction, and 3) The influence of personal competence and learning management together towards the teacher work satisfaction. The sample in this research is 66 teachers. The main method of collecting data used is questionnaire or questionnaire. Data analysis techniques in this study using simple linear regression analysis and multiple regression analysis. The results of this research indicate that: (1) there is a positive and significant influence of personal competence on teacher work satisfaction. (2) there is positive and significant influence of learning management to teacher work satisfaction. (3) there is positive and significant influence of personal competence and learning management together towards teacher work satisfaction of Junior High School at Bandar Sribhawono.